Laugier-Hunziker syndrome in a young girl - Kamaruzaman, Nor Azam; Musa, Noraini (Malaysian Medical Association, 2023)
Laugier-Hunziker syndrome (LHS) is a rare, acquired disorder characterised by circumscribed pigmented macules of the oral mucosa. This rare condition usually occurs on the lips and the acral glabrous skin (mainly fingers and toes). There have been a few instances where fingernail and toenail melanonychia coexist, but not in this patient. Since very similar mucocutaneous lesions are also seen in malignancy syndromes, LHS is an exclusion diagnosis. It occurs mainly in middle-aged individuals with a ratio of approximately of 2:1 between female to male. Nonetheless, cases among children and adolescents were also reported. We describe a case report of a young Malay girl who was incidentally found with multiple oral labial lesions while presented to the clinic with other concerns.